Analisis Determinan Variabel Kinerja Keuangan Terhadap Total Aset Perbankan Syariah - Ramadhani, Febri (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the effect of total financing, CAR and FDR on total assets in Islamic banking in Indonesia. In the study using panel data analysis and the samples used were 4 Islamic banks in Indonesia. Data were obtained from annual financial reports for 10 years, namely from the 2011-2020 period with a total of 40 data. The results showed that simultaneously the variables total financing, CAR and FDR affect total assets. Meanwhile, partially the total financing variable has a significant positive effect on total assets. negative CAR variable is not significant to total assets and FDR has a significant negative effect.